Analisis Hak Para Pekerja Dalam Perusahaan Yang Mengalami Kepailitan - Nurdiannisa, Alifa; Hervinia H, Helen; Ariana H, Jessica; Loren, Medina (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
A company is not always in prime condition because certainly in a company experiencing liquidity problems, declining profitability, and ultimately can be threatened with bankruptcy caused by various factors. The process of bankruptcy of a company is brought to court by appointing a curator. In Indonesia, regulations have been set regarding this bankruptcy process which are contained in Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations. This regulation regulates the rights of workers if they are in a company that is bankrupt so that they know the steps that need to be taken. This study aims so that every worker who experiences something like this knows how the provisions that regulate, the elements that influence and the efforts that can be made in this situation. This study uses a normative juridical method that analyzes the legal norms that have been made. The data source comes from secondary legal data such as Law Number 37 of 2004, Law Number 13 of 2003. The data collection technique is in the form of literature studies. This study resulted in that every company that experiences bankruptcy is required to provide rights to workers who are laid off, namely in the form of pocket money since the bankruptcy decision so that workers' rights must be prioritized, and someone who is appointed to resolve bankruptcy problems is a curator.